Senior High Students’ Level of Satisfaction and Performance toward Work Immersion - Saluria, Raymark Anthony; Mariño, Ednalane Mae (Journal of Interdisciplinary Perspectives, 2024)
The incorporation of Work Immersion as one of the salient subjects in the senior high curriculum aims to develop the full potential of students and prepare them for college education and the world of work. The study sought to determine and evaluate the satisfaction level of Work Immersion students and gauge their performance as perceived by supervisors of the company and industry partners. Utilizing a descriptive survey design, this research was conducted among 94 senior high students who were part of the Off-Campus Work Immersion at Saint Louis School of Don Bosco. The study employed a questionnaire devised by Necio et al. (2022) that measured the level of satisfaction of students toward Work Immersion. Meanwhile, another questionnaire was devised to gauge the performance of students as perceived by the Work Immersion partners. The results showed that the level of satisfaction of students toward Work Immersion is very high. The students manifested a very satisfied experience with their working relationship with supervisors as they assisted them in gaining the knowledge and skills needed for their immersion. Furthermore, the level of performance of Work Immersion students is very high as rated and evaluated by their supervisors. The students gained the abilities and competencies needed to behave professionally in a real-world workplace. The results of the study can be utilized as baseline data for the improvement of the Work Immersion program.